IDENTIFICATION OF ERRORS WITH BCH CODES USING BASICS AND COMPLEMENTARY NORMS OF SYNDROMES - V. K. Konopelko; D. N. Hoang (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The complexity of the norm decoding is exanimated. The results of computational experiments in the norm decoding for BCH codes are presented. Analysis of the results shows that part of the norm instead the whole norm of the syndrome can be used for the identification of multiple errors patterns. Properties of norms of syndrome for BCH codes are identified. Identification based on the combined use of main and supplementary norms if the value of the first component of the syndrome is zero are proposed.